1997
DOI: 10.1038/sj.bjp.0701341
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐independent stimulation of human myocardial phospholipase C by mastoparan

Abstract: 1 Phosphoinositide-speci®c phospholipase C (PLC) is involved in the regulation of many cellular functions. In the myocardium, PLC-generated second messengers play a role in the regulation of contractile function and in the pathophysiology of myocardial hypertrophy. 2 In the present study, the eect of mastoparan, a tetradecapeptide which is capable of activating heterotrimeric G proteins by mimicking the action of an activated receptor, on membrane-bound human myocardial PLC, was investigated in a cell-free ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The cationic tetradecapeptide mastoparan reportedly activates PLD2 in intact mast cells ( Chahdi et al , 2003 ) and we found that it stimulated PtdBut formation in the PLD-specific transphosphatidylation reaction. However, it did not specifically stimulate PLD in P4E6 and PC3 cell lines because GPEtn and PEtn were the main metabolites released suggesting a preferential activation of PLA 2 and PtdEtn-PLC as observed in other cell types ( Argiolas and Pisano, 1983 ; Schnabel et al , 1997 ; Ferry et al , 2001 ). With benign PNT2C2 cells, mastoparan upregulated basal mechanisms of EtnGP turnover because Etn metabolites were released in the same ratio as from unstimulated cells.…”
Section: Discussionmentioning
confidence: 82%
“…The cationic tetradecapeptide mastoparan reportedly activates PLD2 in intact mast cells ( Chahdi et al , 2003 ) and we found that it stimulated PtdBut formation in the PLD-specific transphosphatidylation reaction. However, it did not specifically stimulate PLD in P4E6 and PC3 cell lines because GPEtn and PEtn were the main metabolites released suggesting a preferential activation of PLA 2 and PtdEtn-PLC as observed in other cell types ( Argiolas and Pisano, 1983 ; Schnabel et al , 1997 ; Ferry et al , 2001 ). With benign PNT2C2 cells, mastoparan upregulated basal mechanisms of EtnGP turnover because Etn metabolites were released in the same ratio as from unstimulated cells.…”
Section: Discussionmentioning
confidence: 82%
“…This is inconsistent with any lytic activity of mastoparan [ 58 ], which could result in large linear currents. Rather, in these cells a classic mastoparan mechanism is more likely, direct activation of Gq [ 59 , 60 ] or PLC [ 61 , 62 ] leading to Ins (1,4,5) P3 production and store release followed by CRAC activation [ 63 , 64 ]. In our bulk assays, we do not detect predicted calcium store release in response to mastoparan, possibly due to the sensitivity of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Of note in this regard, actions of mastoparan have been divided into PTx-sensitive, G i -mediated, and PTx-insensitive, G i - independent signaling pathways. Examples of G i -independent mechanisms include: activation of MAP kinase (Miles et al, 2004), phospholipase C (Nakahata et al, 1990; Schnabel et al, 1997), phospholipase D (Mizuno et al, 1998; Chahdi et al, 2003) and two small molecular weight GTP-biding proteins rho and rac (Koch et al, 1991). Whether one of the previously described G i -independent mechanisms of mastoparan action, or another signaling pathway, mediates the PTx-resistant hyperalgesia induced by mastoparan in the control rats not exposed to prior stress or inflammation remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%